Direct and indirect landscape effects on Quercus ilex regeneration in heterogeneous environments. - Puerta-Piñero, Carolina; Pino, Joan; Gómez, José María (Oecologia, 2012)
Understanding how plant-animal interactions shape plant regeneration is traditionally examined at local scales. In contrast, landscape ecologists working at regional scales often have to infer the mechanisms underlying vegetation patterns. In this study, we empirically explored how landscape attributes (patch connectivity, size, shape, irradiance, slope, and elevation) influence biotic interactions in 1- and 2-year seedlings and saplings of Quercus ilex. We combined field data and GIS-based information under a set of five connectivity scenarios, presuming low, intermediate, and long-distance seed dispersal. Our study emphasizes that landscape, apart from its direct effects on plants, plays a key, albeit indirect, role in plant demography through its effects on seed dispersers and predators. Moreover, the effects of landscape on recruitment differed between plant life stages. One-year seedlings and saplings appear to depend more on plant-animal interactions, while 2-year seedlings depend more on irradiance. Differences in patch connectivity resulted in direct and indirect effects on biotic interactions, which, in turn, produced contrasting positive and negative effects on regeneration at different stages of the life cycle. While jays and wild boars seem crucial to all life stages and most of the connectivity scenarios, rodents and herbivores affected only 1-year seedlings and saplings, respectively, and only a few of the connectivity scenarios. By simultaneously including an ensemble of explanatory factors, our study emphasizes that regeneration depends on a set of key drivers, both abiotic (i.e. irradiance) and biotic (i.e. jays and wild boars), whose effects are greatly modulated by landscape traits.
Keywords: Animals; Ecosystem; irradiance; landscape connectivity; Life Cycle Stages; Mediterranean; Passeriformes; Plant Dispersal; Plant–animal interactions; Quercus; Quercus: growth & development; Recruitment; Seedling; Seedling: growth & development; Sus scrofa

Scaling local abundance determinants in mediterranean dung beetles - NUMA, CATHERINE; LOBO, Jorge M.; VERDÚ, JOSÉ R.; Uma, Catherine N. (Insect Conservation and Diversity, 2012)
Abstract. 1. We study the factors that contribute to the variation in the local abundance of dung beetle species inhabiting Cabañeros National Park, a Mediterranean reserve in Central Spain. The relative roles of five different groups of explanatory variables (climatic, local-scale vegetation, landscape-scale vegetation, landscape connectivity and trophic resources) were assessed for 27 sampling sites established by a nested hierarchical sampling design that considered three regional landscapes (woodland, scrubland, grassland) and three local habitat types (forest, scrub, pasture) within each landscape. 2. Connectivity variables related to the spatial configuration of closed vegetation and distance to patches of open or closed vegetation were the best predictors of the species abundance. Precipitation was the most important climatic variable, whereas grassland area at the local- or landscape-scale and woodland area at the landscape-scale were the most important vegetation variables. Dung resources variables had the lowest explanatory ability. 3. More than 60% of the models explained more than 70% of the total variability. Observed and predicted abundance were highly and positively correlated and the mean percentage of absolute predictive errors was approximately 50%. Low-abundance observations had higher predictive errors and model accuracies seemed to be lower for species with narrow distributional ranges and presence in a high number of sampling localities. 4. Mediterranean ecosystems contain a diverse assemblage of dung beetle species whose composition and abundance are influenced by a variety of factors operating across different spatial scales. The most important variables are the spatial configuration and the habitat connectivity around each locality.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Abundance models; Cabañeros National Park; landscape connectivity; landscape scale; Scarabaeoidea; species traits